The place of biology and anthropology in Dewey's ethical project - López, Federico E. (2018)
This article focuses on Dewey's uses of scientific and evolutionary insights in ethics. To begin with, an overview of Dewey's ethics is presented. It is pointed out that his position on ethics must be understood as a political project that advocates for the use of scientific knowledge in dealing with ethical and political conflicts. In turn, this point of view is based on the thesis of the material and methodological continuity between science and ethics. The second section addresses the question of Dewey's approach to the bond of science and philosophy in general, and the value of evolutionary theory and anthropology to ethics in particular. Contrary to some current interpretations, it is argued that, according to Dewey, biology and evolution theory do not have the only nor the final say on ethics, and that in his opinion the relevance of anthropology and social sciences must not be overlooked. Moreover, it is argued that the material continuity between science and ethics highlights the importance of a scientifically informed ethical deliberation when facing ethical problems, while the methodological continuity shows how it is possible to reach sound conclusions in ethics but also the relevance of what can be called genealogical critiques concerning inherited moral beliefs.
O foco deste artigo consiste nos usos dos insights científico e evolucionário na ética de Dewey. Para começar, apresenta-se uma visão geral da ética de Dewey. Salienta-se que a posição dele na ética deve ser entendida como um projeto político que advoga para o uso do conhecimento científico ao lidar com os conflitos éticos e políticos. Por sua vez, esse ponto de vista baseia-se na tese da continuidade material e metodológica entre a ciência e a ética. A segunda parte trata da questão da abordagem de Dewey ao vínculo da ciência e da filosofia, em geral, e o valor da teoria da evolução e da antropologia à ética, em especial. Contrário a algumas interpretações atuais, argumenta-se que, segundo Dewey, a biologia e a teoria da evolução não possuem a única nem a palavra final sobre a ética, e que em sua opinião, a relevância da antropologia e das ciências sociais não deverão ser negligenciadas. Além disso, argumenta-se que a continuidade material entre a ciência e a ética destaca a importância de uma deliberação ética cientificamente informada quando os problemas éticos são enfrentados, enquanto a continuidade metodológica mostra como é possível atingir conclusões corretas na ética, mas também, a relevância que pode ser denominada de críticas genealógicas referentes às crenças morais hereditárias.
Keywords: Anthropology; Dewey; Ethics; Evolution theory; Antropologia; Dewey; Etica; Teoria da evolução^lpt